Predictors of overweight and obesity among postgraduate African students in a public university in Malaysia, 2017 - Tukur, Nura; Ismail, Suriani; Abdul Manaf, Rosliza (Community Health Society Malaysia, 2017)
Background: Globally, obesity is one of the major public health problems and is an independent risk factor for cardiovascular disease (CVD). The risk for non-communicable diseases (NCDs) increases with each rise in body mass index (BMI). Hence, obesity is considered as one of the leading risk factors for mortality due to NCD. Seventy percent (70%) of 56.4 million global deaths were due to NCDs in 2015 alone, with over three quarters (30.7million) of these mortalities happened in low and middle-income countries. Several studies have reported the association between overweight, obesity and several factors, for example, the socio-demographic factors, behavioural factors, eating pattern and psychological factors. Subsequently, this study aims to investigate the predictors of overweight and obesity among African postgraduate students in Public University Malaysia. Materials and Methods: A cross-sectional study was conducted using a self-administered structured questionnaire. All registered full-time post graduate African students were included in the study. While the exclusion criteria were pregnant students, physically challenged that cannot stand without support and registered students that were on deferment or long medical leave. The study analysis was done using Statistical Package for Social Sciences (SPSS) version 23. Descriptive statistics (frequency and percentage) was used to summarise categorical data while. Multiple logistic regressions were used to determine predictors of overweight and obesity. Result: Study respondents were 559 African post-graduate students in a public university in Malaysia who a selected randomly from list of post graduate students, out of which 77.3% were males and 22.7% were females. Overall there were 29.3% overweight respondents while 6.1% were obese. In multiple logistic regression, the significant predictors were: age group of 30 – 39 years (AOR=2.209; 95%CI=1.048 – 4.657) and 40 – 49 age group (AOR=2.530; 95%CI=1.043 – 6.134), gender (AOR=2.037; 95%CI 1.130 – 3.672), marital status (AOR=3.686; 95%CI=1.783 – 7.620), low physical activity level (AOR=2.478, 95%CI=1.191 – 5.157) and alcohol consumption (AOR=2.999, 95%CI=1.667 – 5.396). Conclusion: In conclusion, the males had a higher prevalence of overweight and obesity than females. Advancing age, being male gender, being married, as well as alcohol consumption were found to predictors of overweight and obesity. The study also found a high-level physical activity to be protective against overweight and obesity.